PERFORMANCE ANALYSIS COMPRESSIVE STRENGTH AND WATER ABSORPTION OF RICE HUSK WASTE AS A MIXED MATERIAL IN PAVING BLOCK PRODUCTION FOR THE RICE MILLING INDUSTRY - Sudarno P Tampubolon; Deviana Pratiwi Munthe (LPPM Universitas Negeri Jakarta, 2026)
The utilization of rice husk waste in Indonesia remains very limited, despite rice production being carried out three times a year, which significantly increases the volume of grain and straw. Rice husk waste can be processed through various methods, including its use as a mixture in compost and paving block production, with the aim of reducing environmental impacts. In the rice milling process, approximately 20–30% of the initial grain weight is obtained as husks, 8–12% as bran, and 50–65% as milled rice. The high proportion of husks generated can potentially cause environmental problems if not properly managed. Therefore, this research utilize rice husk waste by burning it at temperatures of 600°C, where the combustion process produces Rice Husk Ash (RHA) with pozzolanic properties. RHA contains a high silica content, making it a suitable supplementary material for paving block production. Based on the experimental results, paving blocks with a 10% addition of RHA achieved an average compressive strength of 15.4 MPa, which meets the criteria for C quality paving block. The water absorption values ranged from 9% to 21%, with an average of 14%. Based on the results of this research indicated that incorporating rice husk ash as an additive in paving block manufacturing can enhance material quality, producing compressive strength that exceed the standard requirements for C quality concrete.